Conceptualization criteria with an organic approach for the formulation of the architectural party in students of the Architecture Workshop VI of the Private University of Tacna - 2015 - Delgado Becerra, Dayker Nivardo (2016)
Objective: The aim of this investigation is to determine if the application of conceptualization criteria with an organismic approach, enhances the Formulation of Architectural prospect of the workshop VI students of the Private University of Tacna. Method: The study because of its purpose is a basic type and because of the level of knowledge is an explanatory type. The design is experimental because we worked with a group and measured before and after. The population consisted of 28 male and female participants, evaluated by the technique of observation and as an instrument Rubric an Analytical Performance. Results: Regarding the results, after the experience, "very appropriate" formulations had a slight increase (from 1.2% to 3.6%), appropriate increased significantly (from 4.2% to 38.7%), as to the "Inadequate "an increase from appreciated the" very inadequate "(from 32.5% to 49.7%), which fell significantly (from 62.2% to 8%). Conclusions: In general, the formulation of the Architectural Prospect before applying the criteria was inadequate conceptualization (mean 5.32), improving (average 16.53) after the experience. The difference between the formulation of the Architectural Prospect before and after the application of the criteria is significant (average 11.21) (p <.01) Therefore, the investigation leads to the conclusion that the application of the criteria Concept with organismic approach is effective as possible to improve the formulation of Architectural Prospect.